Application of Scrabble Game in Improving Learning of Simple Sentence Structure on the Student with Hearing Impairment - Endang Rusyani; Rina Maryanti; Sri Rahayu; Risti Ragadhita; Dwi Fitria Al Husaeni; Budi Susetyo (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to analyze the application of scramble games on the learning ability to compile simple sentence structures in students with hearing impairment. Scramble Game is the learning method that was chosen to convey the material for constructing simple sentences in this study. The research method used in this study was an experimental method with a Single Subject Research (SSR) design which was conducted in three stages, namely: 1) learning in initial condition (before intervention), 2) learning in the intervention condition, and 3) learning after the intervention. The research subject is a second-grade student with hearing impairment at a special junior high school in Cirebon Regency. The Scramble Game method is prepared by making picture cards containing simple words to be arranged into coherent sentences. The results of the study show that after being given learning with the scramble game with picture word cards, the student with hearing impairment experienced increases in their ability to compose simple sentence structures. This study provides alternative learning strategies, especially for teachers who teach the student with hearing impairment.